Pengaruh Pemberian Ekstrak Rumput Bambu (Lophatherum gracile) sebagai Hepatoprotektor pada Mencit Jantan (Mus musculus) - Putra Fauzi, Zidan Imana; Suryani, Des (Universitas Muhammadiyah Sumatera Utara, 2027)
Abstract: The use of paracetamol in toxic doses can cause impaired liver function. Bamboo grass is a plant that contains antioxidants, so it can be a hepatoprotector in protecting the liver from damage caused by paracetamol. The dose of Lopatherum gracile as a hepatoprotector has been studied in the dose range of 200 mg/kg body weight and 800 mg/kg body weight, with an effective dose result of 800 mg/kg body weight. The purpose of this study was to determine the effective dose of the hepatoprotector of bamboo grass extract against paracetamol-induced liver function in mice. This study is a true experiment with a post-test-only control group design. 5 groups were given treatment for 7 days, namely the negative control group (C-), positive control (C+), treatment 1 (T I): 400 mg/kg body weight, treatment 2 (T II): 600 mg/kg body weight, and treatment 3 (T III): 800 mg/kg body weight. The SGOT and SGPT levels between groups were analysed by one-way ANOVA and post hoc Bonferroni. The results of the ANOVA test showed a significant difference in the level of SGOT and SGPT, namely p=0.001. The post hoc test showed no significant difference in SGOT and SGPT levels between T(II) and T(III), with negative controls of p:0.242, and p:0.100, and there was no significant difference in average SGOT between T2 and T3. The effective dose of hepatoprotector of bamboo grass extract in a group of paracetamol-induced mice was 600 mg/kg body weight.